CLICKBAIT SEBAGAI STRATEGI FRAMING BERITA DALAM MEDIA DARING TRIBUNNEWS.COM - Apriliyanti, Rizki; Ali Wafa, Mohammad; Muhari; irfani, M. Irfani (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study aims to understand how the use of clickbait headlines in Tribunnews.com's news content influences the level of trust among Communication Science students at UNISKA MAB toward the information presented. The growing prevalence of clickbait in online media is seen as effective in attracting readers' attention but raises concerns regarding information accuracy, journalistic ethics, and public trust. This research employs a qualitative approach using a case study method, involving eight Communication Science students selected purposively as informants. Data were collected through observation, documentation, and in-depth interviews. The findings indicate that most students are aware of the presence of clickbait, particularly in entertainment and lifestyle sections. While catchy headlines are acknowledged to successfully capture attention, misleading content that does not match the headline tends to reduce credibility and foster distrust. The study reveals a difference in perception between students frequently exposed to clickbait and those who are not. The former group tends to be more skeptical yet tolerant, while the latter prioritizes content accuracy and integrity. The study recommends enhancing media literacy among students and encouraging onli ne media platforms to balance attractive headlines with factual and reliable content. Keywords: Clickbait, Media Trust, Tribunnews.Com, Online Media